Enhancing LEACH Protocol with Multi-Criteria Decision Making for Prolonged Network Lifetime in WSNs - Altaha, Mohammed A.; Al Ali, Ghazwan Abdulnabi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
Wireless Sensor Networks (WSNs) have become a crucial solution for monitoring across diverse environments and consist of tiny sensor nodes that autonomously gather data on the environment. Energy depletion is a looming challenge, as sensor nodes rely heavily on their batteries, and once exhausted, the entire network can collapse prematurely. The Low-Energy Adaptive Clustering Hierarchy (LEACH) protocol is a cornerstone in energy-efficient routing protocols for WSNs. However, the Cluster Head (CH) selection process in the traditional LEACH protocol relies on a probabilistic model for CH selection, where each sensor has an equal chance of becoming a CH based on a fixed threshold. To address these issues, this paper proposes an enhanced version of the LEACH protocol by employing a Multi-Criteria Decision-Making (LEACHMCDM) process for CH selection. Instead of relying on random probabilities, the proposed protocol incorporates three key factors: Residual Energy (RE), Distance to the Base Station (DBS), and Node Degree (ND). Nodes with higher RE, shorter DBS, and an optimal ND are more likely to be selected as CHs. Compared to the traditional LEACH, the proposed method significantly improves the network’s lifetime by evenly distributing energy consumption and reducing the risk of premature node failure. Simulation results demonstrate the enhanced protocol’s ability to sustain more operational rounds and achieve higher energy efficiency.